2019
DOI: 10.1002/brb3.1378
|View full text |Cite
|
Sign up to set email alerts
|

Distinct gene alterations between Fos‐expressing striatal and thalamic neurons after withdrawal from methamphetamine self‐administration

Abstract: Background Methamphetamine (Meth) seeking progressively increases after withdrawal (incubation of Meth craving). We previously demonstrated a role of anterior intralaminar nucleus of thalamus (AIT) to dorsomedial striatum (DMS) projections in this incubation. Here, we examined molecular alterations in DMS and AIT neurons activated (identified by neuronal activity marker Fos) during “incubated” Meth‐seeking relapse test after prolonged withdrawal. Methods We trained male rats to self‐administer Meth or saline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Given our previous work and work from others indicating a role for Grin1 /NR1 in cocaine seeking and the efficacy of exercise in reducing cocaine seeking ( 18 , 70 , 74 ), Grin1 transcription was visualized using IGV. This analysis revealed that the normalized mapped read densities for the sedentary and exercise conditions varied significantly by exon ( Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…Given our previous work and work from others indicating a role for Grin1 /NR1 in cocaine seeking and the efficacy of exercise in reducing cocaine seeking ( 18 , 70 , 74 ), Grin1 transcription was visualized using IGV. This analysis revealed that the normalized mapped read densities for the sedentary and exercise conditions varied significantly by exon ( Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…A challenge for treating MA abuse is recurrence during abstinence ( Li X. et al, 2019 ). Although many factors contribute to recurrence of MADs, a possible key predictor is impulsivity ( Ahn et al, 2016 ; Vassileva and Conrod, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the METH-induced conditioned place preference (CPP) model, an increased histone 3 acetylation was identified in the limbic forebrain of mice and found in specific gene-promoter regions related to synaptic plasticity, such as Nrxn, Gria1, Grin2a, and Grin2b, thus indicating its essential role in METH dependence ( 15 ). An increased expression of HDAC3 mRNA has been noted in Fos-positive neurons in the dorsomedial striatum after withdrawal following METH self-administration ( 16 ). Studies have shown that sodium butyrate, a non-selective inhibitor of class I/II HDACs, can help overcome a previously established CPP and suppress the reinstatement of METH-induced CPP ( 17 ).…”
Section: Introductionmentioning
confidence: 99%